Neonatal birth trauma: incidence and predisposing factors - Asril Aminullah; Novik Budiwardhana; Agus Firmansyah (Paediatrica Indonesiana, 2003)
Background The incidence of birth trauma and its predisposingfactors at a major teaching hospital in Indonesia had not been reported.Objective To find the incidence of birth trauma, calculate a riskassessment of predisposing factors, to study whether cesareansection lowers birth trauma, and to identify the variety of morbidityand mortality due to birth trauma.Methods The incidence was studied retrospectively from 4843medical records from January 2000 through June 2001 using theICD-10 classification. Birth trauma cases were then included in acase-control study for a risk assessment profile of predisposingfactors with logistic regression analysis.Results Three hundreds and thirty five out of 4843 neonates wereidentified to have birth trauma. Analysis revealed that forcepsextraction (OR=48.29; p<0.01), vacuum extraction (OR=25.37;p<0.01), breech vaginal delivery (OR=3.94; p=0.03), and cesareansection (OR=3.44; p<0.01) were significant risk factors.Macrosomic infant (OR=3.86; p=0.04) was also significant. Birthinjury to face (ICD-10 code P15.4) was the most common finding,followed by cephalhematoma and bruising of the scalp.There was no mortality due to birth trauma.Conclusions The incidence of birth trauma was still high. Cesareansection was found to be one of the risk factors, butcompared to forceps and vacuum extraction, the risk of traumais considered to be more acceptable.